Analisis dan Kontribusi Sektor Basis Non-Basis: Penentu Potensi Produk Unggulan Kabupaten Kebumen - Marynta Putri Pratama (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The research method used in this study is LQ Analysis to determine changes in the structure/performance of the regional economy to a higher economic structure (provincial or national) as a reference and Shift Share Analysis to determine the performance or work productivity of the regional economy by comparing it with larger regions (regional or national level). This study takes secondary data obtained from BPS data. Based on the results of the study note that (1) the commodity of Corn, Cassava, Sweet Potatoes, Peanuts, and Soybeans have a number of LQ> 1. These results describe these five products being the base products in Kebumen Regency. Calculation of total shift-share that triggers rapid growth for Kebumen Regency is the commodity of paddy, maize, cassava, soybeans, and green beans. While sweet potatoes and peanuts have not been able to trigger growth in the growth of the food crops sub-sector in Kebumen Regency